Direct Spectrophotometric Determination of Glimepiride in Pure Form And Pharmaceutical Formulations Using Bromocresol Purple - Ramadan, Abdul Aziz; Zeino, Souad (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
A simple, direct and accurate spectrophotometric method has been developed for the determination of Glimepiride (GLM) in pure and pharmaceutical formulations by complex formation with bromocresol purple (BCP). The method involves the formation of a yellow ion-pair complex between BCP with glimepiride at pH<3,8; after reacting GLM with Na2CO3 to give C24H33N4H+O5NaS which is extracted by chloroform. The formed complex [GLM]:[ BCP] was measured at lmax 418 nm against the reagent blank prepared in the same manner. Variables were studied in order to optimize the reaction conditions. Molar absorptivity (e) for complex was 20600 L.mol-1.cm-1. Beer’s law was obeyed in the concentration range of 1.226 – 46.608 mg.mL-1 in present of 5.0x10-4 mol/l of BCP with good correlation coefficient (R2= 0.9997). The relative standard deviation did not exceed 3.6%. The limit of detection (LOD) and the limit of quantification (LOQ) were 0.15 and 0.46 mg.mL-1, respectively. The proposed method was validated for specificity, linearity, precision and accuracy, repeatability, sensitivity (LOD and LOQ) and robustness. The developed method is applicable for the determination of GLM in pure and different dosage forms with average assay of 98.8 to 102.0% and the results are in good agreement with those obtained by the RP-HPLC reference method.